2015
DOI: 10.1108/ajb-01-2014-0001
|View full text |Cite
|
Sign up to set email alerts
|

Schedule preferences, congruence and employee outcomes in unionized shift workers

Abstract: Purpose – Employees working nonstandard schedules outside the daytime hours of the Monday-Friday work week are increasing. Using Social Exchange Theory (SET), the purpose of this paper is to hypothesize relationships between scheduling preferences, attitudes, and retention indicators. Design/methodology/approach – Survey data were collected from 343 US Postal Service mail processors (day, evening, or night shift; all shifts working weeke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
1
1
0
1
Order By: Relevance
“…A comparison of the respondents with the population showed that more senior, older, higher paid, female, and full-time employees were more likely to return the survey and thus our sample is more representative of stablecareer grocery store employees than the entirety of grocery store employees, which includes more young part-time workers with high-turnover rates. These differences are similar to those of other surveys of retail union members (e.g., Wittmer et al, 2015). Four months later, the second survey was mailed to the 985 members who returned the first survey and were still employed in the organization.…”
Section: Sample and Data Collectionsupporting
confidence: 78%
See 1 more Smart Citation
“…A comparison of the respondents with the population showed that more senior, older, higher paid, female, and full-time employees were more likely to return the survey and thus our sample is more representative of stablecareer grocery store employees than the entirety of grocery store employees, which includes more young part-time workers with high-turnover rates. These differences are similar to those of other surveys of retail union members (e.g., Wittmer et al, 2015). Four months later, the second survey was mailed to the 985 members who returned the first survey and were still employed in the organization.…”
Section: Sample and Data Collectionsupporting
confidence: 78%
“…Second, researchers have used employees' attempts to change schedules as a proxy for schedule misfit. For example, Wittmer, Shepard, and Martin (2015) captured whether schedule preferences were met by measuring whether employees requested to change their work schedules, finding that these bids were related to attitudes towards schedules, particularly for those working non-day shifts. However, this strategy may underestimate misfit as employees may be unable or unwilling to request a schedule change even if fit is poor due to organizational norms or poor relationships with supervisors.…”
Section: Schedules and Work-family Person-environment Fitmentioning
confidence: 99%
“…Maka dari itu, aktivitas penjadwalan ini berkaitan dengan penugasan dan aktivitas petugas, crew, maupun staf karena dianggap mampu meningkatkan produktivitas karyawan yang kemudian dapat memberikan kontribusi pada kinerja organisasi apabila dilakukan dengan tepat(Wittmer et al, 2015; Suptihati, 2014). Lebih dalam dijelaskan dalam penelitianBilling et al (2013) bahwa penjadwalan kegiatan dapat menurunkan hal-hal negatif antara struktur tugas dan keterlibatan pekerjaan yang kemudian dapat meningkatkan kinerja baik dari suatu perusahaan.…”
unclassified